USING YOUTUBE VIDEOS IN IMPROVING STUDENTS’ SPEAKING SKILLS (Karya Ilmiah Mahasiswa (KIMA), 2026)
The objectives of this research are to know the effectiveness of using YouTube videos to develop students' speaking skills through procedure text and To know the difficulties the students use YouTube videos to improve students speaking skills at .This study used a quantitative method with approach pre-experimental research from the results of research conducted for 4 weeks with 8 meetings showed that using youtube videos effective in improving students' speaking skills This can be seen trom the post test average value which higher than the pre test (52.73 < 71.64) besides that the statistical calculation of the hypothesis by used paired sample test showed the value of significant (2-tailed) is 0.00 < 0.05, the null hypothesis (HO) was rejected where as the alternative hypothesis (H1) was accepted which means there is significant effect of using Youtube video through asked and answered quisionnaire in teaching procedure text and the results of this quisionnaire showed that there were no obstacles or problems that students feels by used this method it can be seen from the last perception "I have some problem used the youtube media in learning process" and the data saws 40.90% of students choose disagree, 36.36% undecided 18.18% agree and 4.54% strongly disagree. From the resulting questionnaire, some students didn't have a problem with using the YouTube video in the learning process.